Effect of canine mesenchymal stromal cells loaded with paclitaxel on growth of canine glioma and human glioblastoma cell lines. (May 2017) - Bonomi, A.; Ghezzi, E.; Pascucci, L.; Aralla, M.; Ceserani, V.; Pettinari, L.; Coccè, V.; Guercio, A.; Alessandri, G.; Parati, E.; Brini, A.T.; Zeira, O.; et al.
Highlights: Canine mesenchymal stromal cells (cMSCs) were isolated from bone marrow (BM-cMSCs) and adipose tissue (AT-MSCs). BM-cMSCs and AT-cMSCs were able to take up and release paclitaxel (PTX), a chemotherapeutic agent. cMSCs loaded with PTX (cMSCs-PTX) inhibited proliferation of a canine glioma cell line and two human glioblastoma cell lines. The potential therapeutic value of canine cMSCs-PTX should be investigated. Abstract: This study investigated whether canine mesenchymal stromal cells (cMSCs) are able to take up and release paclitaxel (PTX) in active form, and therefore whether they have potential as a tool for therapeutic delivery of this drug. cMSCs from bone marrow and adipose tissue were isolated, expanded and characterised phenotypically. cMSCs were loaded with PTX (cMSCs-PTX) and their capacity for release of PTX was determined by their effect on proliferation of cancer cells. cMSCs-PTX derived from bone marrow and adipose tissue were able to take up and then release active PTX. cMSCs-PTC inhibited proliferation of the canine glioma cell line J3T, and the human glioblastoma cell lines T98G and U87MG. The potential of canine cMSCs-PTX for treatment of canine gliomas should be investigated further.